Reference-dependent effects of unemployment on mental well-being - Martina Grunow (Universität Augsburg, Institut für Volkswirtschaftslehre, 2014)
This paper provides an empirical analysis of reference-dependent effects of unemployment on mental well-being. We show that the negative effect of unemployment on mental well-being depends on expectations about the future employment status. Several contributions to the literature have shown that the perception of the individual employment status depends on the surrounding unemployment rate. We argue that expectations are a possible link between unemployment rates and the individual employment status regarding changes in mental well-being. Theoretical foundation comes from models for reference-dependent preferences with endogenous reference points. We provide a simple theoretical model to motivate and structure the empirical analysis. Using data from the German Socio-Economic Panel, we estimate a pairwise interacted model for employment status and expectations over two time periods. Life satisfaction is used as a proxy for mental well-being. To identify a causal effect of unemployment, expectations and their interactions on mental wellbeing, the analysis relies on fixed effects and exogenous entries into unemployment due to plant closures. We confirm the standard result that unemployment has a negative effect on mental well-being. Furthermore, the results deliver empirical evidence for reference-dependent effects of unemployment on mental well-being. We find that becoming unemployed unexpectedly is more severe as if the unemployment was expected. Therefore, this paper contributes to the understanding of how mental well-being is affected by unemployment and delivers empirical support for the theoretical models of reference-dependent preference wit endogenous reference points determined by expectations.
urn:nbn:de:bvb:384-opus4-710942
Keywords: C23; D03; D84; I10; I18; J01; J60; 330; Subjective Well-Being; Unemployment; Reference-Dependence; Reference Points